Importance-performance ratings for environmental practices among Hong Kong professional-level employees. (1st December 2015) - To, W.M.; Lam, K.H.; Lai, T.M.
Abstract: The environmental performance of organizations is an increasing focus in cleaner production. This paper explores how the importance and performance of environmental practices were perceived among professional-level employees in Hong Kong, China. Based on a literature review on sustainable development and environmental management, we developed a structured questionnaire to measure respondents' perceptions towards environmental practices. Using responses from 348 professional-level employees in Hong Kong organizations, we employed importance-performance analysis for identifying some improvement opportunities. In addition, we applied exploratory factor analysis to identify the underlying environmental factors based on the importance ratings. Results of the study demonstrated that the performance of environmental practices was strongly associated with perceived importance of environmental practices. As environmental practices, it was found that Hong Kong organizations and employees primarily focused on saving paper and energy resources. However, they are not embracing the concept of green value chain and have yet to engage their suppliers to go green. This paper contributes to identify the key internal and external factors of environmental practices. Highlights: The performance of environmental practices is related to perceived importance. Hong Kong organizations primarily focused on saving paper and energy resources. Organizations have yet to treat their suppliers as 'green partners'. Professional-level employees can affect firms' environmental practice & performance.